Service quality measurement towards customer satisfaction - Deutsche Post (DHL) in Asia Pacific - Poh, Cecilia Shiow Huei; Razalli, Mohd Rizal (2012)
The purpose of this paper is to analyze the factors that contribute to service quality which are timeliness, condition/ accuracy of order, and quality of information towards a greater customer satisfaction.in DHL’.With the 38% dominant the Asia Pacific express market, DHL has a need to identifies significantly improve the customer satisfaction as a key benefits of logistics service quality.The company has find out the causes that affect the quality of the services to have a sustainable business. This paper will discuss about the DHL service performance by interview with the DHL Alor Star branch and reviewing the literature as a secondary resource.